Armazenabilidade de sementes de cafeeiro em diferentes estádios de maturação e submetidas à diferentes métodos de secagem - Veiga, André Delly (2005)
The harvesting time and drying methods may influence the quality of coffee seeds during storage. Thus, this work was conducted with the objective of understand the effects of maturation stages and drying methods on the physiological quality and storability of coffee seeds. The experiments were performed at the Seed Analysis and Electrophoresis Laboratory of the Department of Agricultural of UFLA. The fruits of the cultivar Rubi were harvested, depulped and the mucilages removed by fermentation at 30¨¬C for 24 hours and the seeds washed and let on paper for removal of the water. The seeds were submitted to conventional drying (under shade) and drying in stationary drier at temperature of 35¨¬C. As a control, seeds with no drying were analyzed. The evaluations were done soon after the drying treatments and after four and eight months of storage. The seeds were stored at 10¨¬C in air-tight plastic packages. The germination test, radicle protrusion, seedling dry matter, emergence index speed, electric conductivity, electrophoresis analyses of heat-resistant proteins and quantification of endo-¥â-mannanase activity were the parameter evaluated. The design was completely randomized with 2 (maturation stages) x 3 (dryings) x 3 (storage time) factorial scheme with four replications. In general, the seeds submitted to drying lost vigor and viability, mainly when harvested in the stage characterized as green-cane, the fast drying showed to be harmful to the physiologic quality of seeds. The presence or the intensity of the bands of heat-resistant proteins was associated with drying of seeds. The activity of endo-¥â-mannanase was higher in seeds harvested at the cherry stage than in seeds harvested at the green-cane stage. There was an increase in the endo-¥â-mannanase activity as the storage period increased.